Anxiety level and correlates in methamphetamine-dependent patients during acute withdrawal. Issue 15 (April 2017) - Su, Hang; Zhang, Jie; Ren, Wenwei; Xie, Ying; Tao, Jingyan; Zhang, Xiangyang; He, Jincai
Abstract : Abstract: Anxiety is often a core element of withdrawal symptoms; however, risk factors associated with anxiety symptoms during the early stage of withdrawal in methamphetamine (METH) users are not well understood. Two hundred ten METH-dependent subjects who had been abstinent for 1 to 7 days were recruited. We used a set of self-administrative questionnaires eliciting information on sociodemographics, detailed drug use history and anxiety. Beck Anxiety Inventory (BAI) was used to measure anxiety symptoms. METH users had a mean BAI score of 6.9; 72 (34.3%) of the study sample had anxiety symptoms during acute METH withdrawal, including 42 (20.0%) with mild anxiety, 25 (11.9%) with moderate anxiety, and 5 (2.4%) with severe anxiety. In addition, gender (female), higher frequency of drug use, and history of polysubstance use were significantly correlated with anxiety symptoms during acute METH withdrawal. Anxiety symptoms appear to be common during the first week of METH abstinence, and several risk factors are identified.